2000
DOI: 10.1590/s0036-46652000000500003
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrarily primed PCR fingerprinting of RNA and DNA in Entamoeba histolytica

Abstract: Differences were detected in the gene expression of strains of E. histolytica using RNA (RAP-PCR) and DNA fingerprinting (RAPD). Analysis of the electrophoretic profiles of the gels revealed some polymorphic markers that could be used in the individual characterization of the strains. The 260 bands generated by using five different primers for RAP-PCR, as well as RAPD, were employed in the construction of dendograms. The dendogram obtained based on the RAPD products permitted the distinction of symptomatic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
(18 reference statements)
0
5
1
2
Order By: Relevance
“…One previous study using RAPD also identified EH (Rahman) as distinct from virulent EH strains (64). However, unlike our study, they were not able to identify the genetic regions that differentiated EH (Rahman) from the other EH strains.…”
Section: Vol 4 2005 Genotypes Of Entamoeba Correlate With Virulencecontrasting
confidence: 97%
See 2 more Smart Citations
“…One previous study using RAPD also identified EH (Rahman) as distinct from virulent EH strains (64). However, unlike our study, they were not able to identify the genetic regions that differentiated EH (Rahman) from the other EH strains.…”
Section: Vol 4 2005 Genotypes Of Entamoeba Correlate With Virulencecontrasting
confidence: 97%
“…Although limited, these data indicate that the extensive genetic diversity identified by analysis of repetitive regions may not be indicative of a genome-wide phenomenon. A number of studies have attempted to identify an association between parasite genotype and the clinical phenotype and although most have failed, two studies (one using RAPD analysis of amebic isolates and one using PCR and RFLP analyses of the serine-rich E. histolytica protein [SREHP]) did give some preliminary indication that it may be feasible to find a genotypic pattern predictive of a phenotypic outcome (7,64). Host factors that contribute to variable disease manifestations have also been studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of nonrepetitive loci have revealed very limited polymorphisms (3,6). There is no definitive correlation between genotypes of E. histolytica strains and their clinical manifestations; however, three studies preliminarily indicated that genotypic patterns may be predictive of a clinical outcome (1,16,18). To get an improved perspective of genetic variability in nonrepetitive genomic regions, we sequenced 9,077 bp (6,621 bp coding and 2,456 bp noncoding) from each of 14 E. histolytica isolates.…”
mentioning
confidence: 99%
“…The amplification products are then resolved in gels and recorded by a variety of techniques (reviewed in Caetano-Anolles 1996). Presence or absence of DNA bands in the gel may be used as RAPD markers to study inter-and intra-specific genetic variations (M'Ribu and Hilu 1994), for the identification of specific genes (Paran et al 1991;Martin et al 1991), and to study the pattern of gene expression (Valle et al 2000). Our results with a limited number of G. biloba specimens indicated a high degree of genetic homogeneity among plants grown in certain areas, although high levels of overall genetic diversity may exist in the species.…”
Section: Introductionmentioning
confidence: 73%